The HubBLe Trial: haemorrhoidal artery ligation (HAL) versus rubber band ligation (RBL) for symptomatic second- and third-degree haemorrhoids: a multicentre randomised controlled trial and health-economic evaluation - Steven Brown; Jim Tiernan; Katie Biggs; Daniel Hind; Neil Shephard; Mike Bradburn; Allan Wailoo; Abualbishr Alshreef; Lizzie Swaby; Angus Watson; Simon Radley; Oliver Jones; et al. (Health Technology Assessment, 2016)
Background: Optimal surgical intervention for low-grade haemorrhoids is unknown. Rubber band ligation (RBL) is probably the most common intervention. Haemorrhoidal artery ligation (HAL) is a novel alternative that may be more efficacious. Objective: The comparison of HAL with RBL for the treatment of grade II/III haemorrhoids. Design: A multicentre, parallel-group randomised controlled trial. Perspective: UK NHS and Personal Social Services. Setting: 17 NHS Trusts. Participants: Patients aged ≥ 18 years presenting with grade II/III (second- and third-degree) haemorrhoids, including those who have undergone previous RBL. Interventions: HAL with Doppler probe compared with RBL. Outcomes: Primary outcome – recurrence at 1 year post procedure; secondary outcomes – recurrence at 6 weeks; haemorrhoid severity score; European Quality of Life-5 Dimensions, 5-level version (EQ-5D-5L); Vaizey incontinence score; pain assessment; complications; and cost-effectiveness. Results: A total of 370 participants entered the trial. At 1 year post procedure, 30% of the HAL group had evidence of recurrence compared with 49% after RBL [adjusted odds ratio (OR) = 2.23, 95% confidence interval (CI) 1.42 to 3.51; p = 0.0005]. The main reason for the difference was the number of extra procedures required to achieve improvement/cure. If a single HAL is compared with multiple RBLs then only 37.5% recurred in the RBL arm (adjusted OR 1.35, 95% CI 0.85 to 2.15; p = 0.20). Persistence of significant symptoms at 6 weeks was lower in both arms than at 1 year (9% HAL and 29% RBL), suggesting significant deterioration in both groups over the year. Symptom score, EQ-5D-5L and Vaizey score improved in both groups compared with baseline, but there was no difference between interventions. Pain was less severe and of shorter duration in the RBL group; most of the HAL group who had pain had mild to moderate pain, resolving by 3 weeks. Complications were low frequency and not significantly different between groups. It appeared that HAL was not cost-effective compared with RBL. In the base-case analysis, the difference in mean total costs was £1027 higher for HAL. Quality-adjusted life-years (QALYs) were higher for HAL; however, the difference was very small (0.01) resulting in an incremental cost-effectiveness ratio of £104,427 per additional QALY. Conclusions: At 1 year, although HAL resulted in fewer recurrences, recurrence was similar to repeat RBL. Symptom scores, complications, EQ-5D-5L and continence score were no different, and patients had more pain in the early postoperative period after HAL. HAL is more expensive and unlikely to be cost-effective in terms of incremental cost per QALY. Limitations: Blinding of participants and site staff was not possible. Future work: The incidence of recurrence may continue to increase with time. Further follow-up would add to the evidence regarding long-term clinical effectiveness and cost-effectiveness. The polysymptomatic nature of haemorrhoidal disease requires a validated scoring system, and the data from this trial will allow further assessment of validity of such a system. These data add to the literature regarding treatment of grade II/III haemorrhoids. The results dovetail with results from the eTHoS study [Watson AJM, Hudson J, Wood J, Kilonzo M, Brown SR, McDonald A, et al. Comparison of stapled haemorrhoidopexy with traditional excisional surgery for haemorrhoidal disease (eTHoS): a pragmatic, multicentre, randomised controlled trial. Lancet 2016, in press.] comparing stapled haemorrhoidectomy with excisional haemorrhoidectomy. Combined results will allow expansion of analysis, allowing surgeons to tailor their treatment options to individual patients. Trial registration: Current Controlled Trials ISRCTN41394716. Funding: This project was funded by the NIHR Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 20, No. 88. See the NIHR Journals Library website for further project information.